Dynamics of value proposition in emerging B2B platform ecosystems - Ali, Wajahat (My University, 2025)
Digital platforms are reshaping industrial value creation; however, the mechanisms through which value propositions emerge in early-stage business-to-business (B2B) ecosystems remain inadequately theorized. This thesis investigates how diverse stakeholders co-create and progressively refine value propositions in an emerging Finnish biogas platform that spans three Ostrobothnian regions. The study employs an interpretivist abductive single-case design grounded in Service-Dominant Logic and platform-ecosystem theory. Twenty semi-structured interviews with farmers, municipal officials, technology providers, biogas producers, and industrial users were analyzed using the Gioia methodology, which traces first-order actor narratives to second-order theoretical themes. The analysis identifies three interlocking processes: stakeholder-driven value co-creation, platform-enabled value proposition, and external forces that shape platform evolution. Each process is supported by distinct mechanisms such as boundary resource design, trust-building routines, and regulatory sense-making. Together, these processes constitute a dynamic capability termed governance-enabled resource integration, through which architectural decisions, actor engagement, and institutional negotiations co-evolve before strong network effects emerge. The resulting process model clarifies the meso-level “missing middle” between the abstract axioms of Service-Dominant Logic and the technical governance choices foregrounded in platform research. The study advances theory by (i) integrating micro-level boundary resources with macro-level institutional dynamics, (ii) reframing value propositions as relational and co-evolutionary constructs, and (iii) demonstrating how power, trust, and reverse-value risks influence B2B platform trajectories. The findings provide platform orchestrators with a staged roadmap encompassing discovery, design, rollout, and upscaling while helping balance openness with control and sustain complementor engagement in sustainability-oriented industries.
Keywords: value creation; biogas; digitalisation; business-to-business marketing; fi=Taloustiede|en=Economics|; Master’s Programme in Strategic Business Development